(untitled) (Research, Society and Development, 2020)
Objective: To present the development of simulations in situ as a teaching and learning strategy for the development of multidisciplinary teams in Primary Care. Methodology: This work is a descriptive study, of the experience report type, referring to the development of in situ simulations carried out in Primary Care, addressing the welcoming performed by professionals of the Unified Health System, we chose to use an actor as simulated patient. The sample was made for convenience, totaling 40 professionals, in four Basic Health Units in the metropolitan region of Campinas, São Paulo, Brazil. To better assess the flow of users in the unit, from the opening of the form, through screening to the service itself. Results: The evaluation of the simulation was positive, reflecting good performance and enabling better integration of the team, however it demonstrated potential weaknesses in the service flow. Conclusion: This experience proved to be a teaching-learning strategy that enhances the practice of welcoming in Primary Health Care and is feasible to be replicated in other public health services.